(untitled) (Homoeopathy for All, 2022)
The most prevalent age for acne, an inflammatory disorder of the pilosebaceous units, is adolescence. Open (black) and closed (white) comedones, inflammatory papules, pustules, nodules, and cysts are the typical lesions, which may result in scarring and pigmentary alterations. Acne vulgaris is a frequent diagnosis made by a physician for eruptions occurring on the face of teenagers described as “PIMPLE” by a layperson. Homoeopathy treats Acne vulgaris either on the basis of constitutional or therapeutics and achieves great success. Here presenting a case of Miss Xx, age 21 years old female came to OPD with complaints of acne vulgaris cured by constitutional homoeopathic medicine.